Laminar Natural Convection of Newtonian and Non – Newtonian Fluids Inside Triangular Enclosure - Muhadi, Ala′a Abbas (Al-Khwarizmi Engineering Journal, 2007)
In the present work, steady two – dimensional laminar natural convection heat transfer of Newtonian and non-Newtonian fluids inside isosceles triangular enclosure has been analyzed numerically for a wide range of the modified Rayleigh numbers of (103 ≤ Ra ≤ 105), with non-dimensional parameter (NE) of Prandtl – Eyring model ranging from (0 to 10), and modified Prandtl number take in the range (Pr* =1,10, and 100). Two types of boundary conditions have been considered. The first, when the inclined walls are heated with different uniform temperatures and the lower wall is insulated. The second, when the bottom wall is heated by applying a uniform heat flux while the inclined walls at the constant cold temperature. Also, the non-Newtonian fluids under consideration were assumed to obey the Prandtl – Eyring model..The results are presented in terms of isotherms and streamlines to show the behavior of the fluid flow and temperature fields. In addition, some graphics are presented the relation between average Nusselt number and the various parameters. The results show the effect of non – dimensional parameter (NE) on the velocity and temperature profiles. They also show that the average Nusselt number is a strong function of modified Rayleigh number, modified Prandtl number, non-dimensional parameter, and the boundary conditions. Four different correlations have been made to show the dependence of the average Nusselt number on the non-dimensional parameter, the modified Rayleigh and Prandtl numbers.